Evaluation of mechanical properties of carbon nanotubes - Teo, Gerald Jie Kai. (2009)
Ever since carbon nanotubes were discovered in 1991, they have been subjected to numerous tests to establish their mechanical properties. Tests have been conducted independently by many academic, research and government institutions, and their results on Young’s modulus and tensile strength have differed greatly from one another. The single greatest challenge facing researchers today is the handling of single-walled carbon nanotubes (SWCNTs). With a SWCNT diameter of 1nm, it is an extremely difficult task to manipulate nanotubes and to perform mechanical tests on them. In most of the experiments already reported, researchers usually used an Atomic Force Microscope (AFM) setup to load an extremely sharp AFM tip on a cluster of carbon nanotubes. The nanotubes would then be attached to the AFM tip with either a silver glue or electron beam induced deposition (EBID). Recording of the experiments were done with either Transmission Electron Microscopy (TEM) or Scanning Electron Microscope (SEM). In this study, suggestions of new methods are proposed to deal with the difficulties presented by testing nanotubes. This include growing nanotubes from pre-determined openings in a rig, growing of carbon nanotubes on silicon tips to be used as manipulators on other nanotubes or sharpening of such tips with electrical pulses. It is the author’s belief that the methods brought forward in this report are not exhaustive of possible solutions to handle and test the mechanical properties of carbon nanotubes.